2004
DOI: 10.1095/biolreprod.103.023648
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Gravidity Differentially Regulate Expression of Extracellular Matrix Components in the Pregnant Rat Myometrium1

Abstract: Myometrial growth and remodeling during pregnancy depends on increased synthesis of interstitial matrix proteins. We hypothesize that the presence of mechanical tension in a specific hormonal environment regulates the expression of extracellular matrix (ECM) components in the uterus. Myometrial tissue was collected from pregnant rats on Gestational Days 0, 12, 15, 17, 19, 21, 22, 23 (labor), and 1 day postpartum and ECM expression was analyzed by Northern blotting. Expression of fibronectin, laminin beta2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 33 publications
9
100
2
1
Order By: Relevance
“…In our study, artificial maintenance of elevated P4 levels at late gestation (from day 20 to day 23) by daily injections of hormone caused a failure to initiate labor. We showed before that this treatment prevented the increase in the expression of CAPs, AP-1, and ECM genes in the rat myometrium (Piersanti & Lye 1995, Shynlova et al 2004. We have now shown that the administration of P4 also prevented the increase of Tgfb3 mRNA levels at term when compared with vehicle-treated animals (Fig.…”
Section: Figure 1 Illustrates the Expression Ofmentioning
confidence: 51%
See 2 more Smart Citations
“…In our study, artificial maintenance of elevated P4 levels at late gestation (from day 20 to day 23) by daily injections of hormone caused a failure to initiate labor. We showed before that this treatment prevented the increase in the expression of CAPs, AP-1, and ECM genes in the rat myometrium (Piersanti & Lye 1995, Shynlova et al 2004. We have now shown that the administration of P4 also prevented the increase of Tgfb3 mRNA levels at term when compared with vehicle-treated animals (Fig.…”
Section: Figure 1 Illustrates the Expression Ofmentioning
confidence: 51%
“…TGFb3 treatment was also found to stimulate fibronectin expression in human cultured leiomyoma cells (Arici & Sozen 2000). We have reported earlier that expression of fibronectin, as well as major components of basement membrane, namely type IV collagen and laminin, are dramatically TGFb in pregnant myometrium up-regulated prior to and during labor in rats (Shynlova et al 2004). Thus, the parallel increase of TGFb3 and ECM components at late gestation suggests that TGFb3 may mediate ECM induction, providing the mechanism to anchor hypertrophied uterine myocytes in order to produce coordinated, forceful labor contractions.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…18S rRNA is constitutively expressed in rat myometrial cells and has been utilized, in the past, as a loading control for analysis of myometrial gene expression (Mitchell & Lye 2002, Shynlova et al 2004.…”
Section: Northern Blot Hybridizationmentioning
confidence: 99%
“…Myometrial cells increase in number and the expression of anti-apoptotic factors, including BCL2, is increased within these cells contributing to an overall increase in proliferation (Shynlova et al 2006). The next phase is the synthetic phase from D15 to D21, where the protein:DNA ratio in the myometrium is increased, cells hypertrophy and increase their production of interstitial extracellular matrix proteins (ECM) and remodel focal adhesions (MacPhee & Lye 2000, Shynlova et al 2004. In the contractile phase, there is an increased expression of basement membrane matrix proteins such as fibronectin and associated integrin receptors in myometrial cells (Shynlova et al 2004, Williams et al 2005, 2010.…”
Section: Introductionmentioning
confidence: 99%